Building brands through internal stakeholder engagement and co-creation. Issue 6 (1st February 2021) - Merrilees, Bill; Miller, Dale; Yakimova, Raisa
Abstract : Purpose: The purpose of this paper is to better understand the voice of the internal stakeholder in a way that emphasizes the internal stakeholder as an active force and decision maker in brand co-creation, as part of the new emerging paradigm of internal branding. The main aim is to understand the active role of volunteers in internal branding that is in the co-creation of value. A subsidiary aim is to understand why some volunteers engage deeply and seriously in a nonprofit organization while other volunteers seem less connected? Design/methodology/approach: A conceptual framework incorporates several motivators to volunteer-led co-creation. A quantitative, co-variance-based structural equation modelling approach is used on survey data of a sample of 357 volunteers from 14 organizations in the Australian nonprofit sector. Findings: The research findings contribute to the newly emerging internal branding literature focusing on the active co-creation role of internal stakeholders. The main drivers of volunteer co-creation are volunteer engagement, commitment, altruism, values-congruency and brand reputation. Different explanatory mechanisms/motivators apply to each type of volunteer-led co-creation. In a major initiative, the paper demonstrates linkages across the different types of co-creation, with a foundation/pivotal role for one particular type of co-creation, namely, enhanced client-based solutions. Research limitations/implications: The research is restricted to the public sector and further research is needed to test applicability to the private sector. Future studies could continue the initiative in the current study to explore the linkages across co-creation types. Practical implications: Implications depend on which type of co-creation is targeted. Enhancing client-based solutions co-creation requires a very strong role for engaged volunteers. Innovation co-creation requires both engaged volunteers and a propensity to co-create by enhancing client-based solutions. Brand advocacy co-creation is driven by volunteer commitment, altruism and a propensity to co-create innovation. Social implications: A non-profit context ensures major social implications. Originality/value: The study operationalizes the Saleem and Iglesias (2016) new internal branding paradigm framework by demonstrating that brands are built organically by interacting and engaging with internal stakeholders (volunteers in this instance), which, in turn, inter alia, motivates co-creation by such internal stakeholders.